2011
DOI: 10.14430/arctic4119
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Marine Fauna and Flora of Two Nearshore Coastal Locations in the Western and Central Canadian Arctic

Abstract: ABSTRACT. Baseline data on nearshore benthic macrofauna and flora assemblages are necessary for successful environmental monitoring in the Arctic, where major climate and industrial changes are underway, yet to date these environments remain understudied. This study used bottom video and benthic grab samples to compare shallow benthic marine (1 -40 m) floral and faunal distribution and composition in two nearshore locations in the Canadian Arctic with different geomorphic settings. Sachs Harbour, located on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
(74 reference statements)
0
7
1
Order By: Relevance
“…A second concern related to water depth was that the stations sampled in the Iqaluit and Cairn Island regions each covered a broad range of water depths (Iqaluit: 11.5-43 m, Cairn Island: 26-73 m). Brown et al (2011) observed differences in community structure at stations shallower than 10 m compared to stations deeper than 10 m in Gjoa Haven, King William Island in the Canadian Arctic. To address the potential influence of water depth on the sediment and biological analysis for each region between the two time periods, water depth was included as a co-variate in all models and an interaction term (time period ~ water depth) was also included in the models to test whether water depth and time period had an influence on the response variable being examined.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A second concern related to water depth was that the stations sampled in the Iqaluit and Cairn Island regions each covered a broad range of water depths (Iqaluit: 11.5-43 m, Cairn Island: 26-73 m). Brown et al (2011) observed differences in community structure at stations shallower than 10 m compared to stations deeper than 10 m in Gjoa Haven, King William Island in the Canadian Arctic. To address the potential influence of water depth on the sediment and biological analysis for each region between the two time periods, water depth was included as a co-variate in all models and an interaction term (time period ~ water depth) was also included in the models to test whether water depth and time period had an influence on the response variable being examined.…”
Section: Discussionmentioning
confidence: 68%
“…With an increasing concern around climate warming and its predicted impacts on Arctic continental shelf benthos McLaughlin 2001, Piepenburg 2005), there is a growing consensus that long-term studies are required to monitor benthic community change. Many authors have called for such studies (e.g., Cusson et al 2007, Renaud et al 2007, Brown et al 2011, Wassman et al 2011, Grebmeier 2012, Kortsch et al 2012, Renaud et al 2015, Thurstan et al 2015 to understand how benthic communities are linked to environmental processes and how future climate change may influence their distribution, composition, and function (Loeng 2005, Carroll et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of a few prominent algal species, primary producers from the Arctic inshore environment are largely underrepresented in the algal literature. This study provides the first comprehensive account of attached Arctic algae in the Beaufort Sea, which complements qualitative studies that pertain mostly to the benthic North Atlantic flora (Kjellman, 1883;Taylor, 1957;Lee, 1980;Cross et al, 1987;Brown et al, 2011). The Boulder Patch and other sublittoral rocky bottoms across the Arctic coast from near Point Barrow (Konar and Iken, 2005;Mohr et al, 1957) to Camden Bay ( Fig.…”
Section: The Boulder Patch Macroalgae: a Sentinel For Change In Arctimentioning
confidence: 64%
“…;Roberts et al, 2002;Adey and Hayek, 2011;Teichert et al, 2012). Future assessments of crust populations in the Boulder Patch may drastically improve our understanding of ecosystem structure and possible change in the Arctic sublittoral flora and fauna (Borum et al, 2002;Brown et al, 2011). Five species of brown algal crusts, representing five different genera, directly compete with coralline crusts and benthic invertebrates for space.…”
Section: The Algal Crusts: a Distinguishing Feature Of The Arctic Benmentioning
confidence: 99%
“…More recently, a benthic survey identified 57 genera of macrobenthic nematodes in coastal areas of Churchill, Deception Bay, Iqaluit, and Steensby Inlet (Gianasi et al, 2022). Additionally, imagebased surveys (e.g., video or photo transects) of the seafloor have been used to assess shallow macrofauna assemblages in Baffin Island (Ellis, 1960), Lancaster and Eclipse sounds (Thomson, 1982), Resolute Bay (Conlan et al, 1998;Conlan and Kvitek, 2005), and Banks and King William islands (Brown et al, 2011), although they did not fully document the extent of nearshore benthic biodiversity due to the coarse taxonomic resolution associated with these methods.…”
Section: Introductionmentioning
confidence: 99%